Genetic regulation and photocontrol of anthocyanin accumulation in maize seedlings. - Taylor, L P (1990)
The flavonoid pathway leading to anthocyanin biosynthesis in maize is controlled by multiple regulatory genes and induced by various developmental and environmental factors. We have investigated the effect of the regulatory loci R, B, and Pl on anthocyanin accumulation and on the expression of four genes (C2, A1, Bz1, and Bz2) in the biosynthetic pathway during an inductive light treatment. The results show that light-mediated anthocyanin biosynthesis is regulated solely by R; the contributions of B and Pl are negligible in young seedlings. Induction of the A1 and Bz2 genes by high fluence-rate white light requires the expression of a dominant R allele, whereas accumulation of C2 and Bz1 mRNA occurs with either a dominant or recessive allele at R. A1 and Bz2 mRNA accumulate only in response to high fluence-rate white light, but Bz1 is fully expressed in dim red light. Some C2 mRNA is induced by dim red light, but accumulation is far greater in high fluence-rate white light. Furthermore, expression from both dominant and recessive alleles of the regulatory gene R is enhanced by high fluence-rate white light. Seedlings with a recessive allele at R produce functional chalcone synthase protein (the C2 gene product) but accumulate no anthocyanins, suggesting that, in contrast to the R-mediated coordinate regulation of C2 and Bz1 observed in the aleurone, C2 expression in seedlings is independent of R and appears to be regulated by a different light-sensitive pathway.